ARCHITECTURE AND MULTIMODAL STIMULATION IN NEURO INTENSIVE CARE - Carlsson, Dennis (My University, 2012)
From the 1960s to present day there has been several studies conducted on rats subjected to enriched environments that shows the increased brain mass and plasticity within the cortical areas. Stimulating the plasticity can be used to improve the recovery in patients suffering from brain damage. With this research as inspiration participants from the Sahlgrenska university hospital, GU, HDK and Chalmers has started a study called “The effect of directed multimodal stimulation in intensive care”. The question in this study is to investigate whether an enriched environment can improve the experience, recovery and rehabilitation in the patients that has received surgery for subarachnoid haemorrhage (stroke). The primary objective of this master thesis will be to provide a suggestion of how architecture can be used as a mean for enrichment and support other mediums that can be used in this purpose. By using knowledge from Evidence based design and observations from neuroscience in relation to patient’s condition, department requirements, we can create a platform for investigating what an enriched environment can be for the patients. The resent advancements made within the field of neuroscience have attracted an interest from architects resulting in the interdisciplinary field of neuroarchitecture. A secondary objective in this thesis is to investigate the potential and purpose of neuroarchitecture. The results obtained from the study of the enriched patient room at Sahlgrenska can tell us if the enrichment has a positive effect on the recovery, experience and rehabilitation. The benefits of this study could be used as a strong argumentation when it comes to investing in a more stimulating design of new hospital environments. The larger implication that the knowledge of enriched environment brings forth is that we as planners and future participants in the building industry are responsible not only for the health and happiness of our clients but also the environment that influences the development of their brains.
Keywords: Samhällsbyggnadsteknik; Civil Engineering